Seismic structure of the lithosphere beneath NW Namibia: Impact of the Tristan da Cunha mantle plume. (20th January 2017) - Yuan, Xiaohui; Heit, Benjamin; Brune, Sascha; Steinberger, Bernhard; Geissler, Wolfram H.; Jokat, Wilfried; Weber, Michael
Abstract: Northwestern Namibia, at the landfall of the Walvis Ridge, was affected by the Tristan da Cunha mantle plume during continental rupture between Africa and South America, as evidenced by the presence of the Etendeka continental flood basalts. Here we use data from a passive‐source seismological network to investigate the upper mantle structure and to elucidate the Cretaceous mantle plume‐lithosphere interaction. Receiver functions reveal an interface associated with a negative velocity contrast within the lithosphere at an average depth of 80 km. We interpret this interface as the relic of the lithosphere‐asthenosphere boundary (LAB) formed during the Mesozoic by interaction of the Tristan da Cunha plume head with the pre‐existing lithosphere. The velocity contrast might be explained by stagnated and "frozen" melts beneath an intensively depleted and dehydrated peridotitic mantle. The present‐day LAB is poorly visible with converted waves, indicating a gradual impedance contrast. Beneath much of the study area, converted phases of the 410 and 660 km mantle transition zone discontinuities arrive 1.5 s earlier than in the landward plume‐unaffected continental interior, suggesting high velocities in the upper mantle caused by a thick lithosphere. This indicates that after lithospheric thinning during continental breakup, the lithosphere has increased in thickness during the last 132 Myr. Thermal cooling of the continental lithosphere alone cannot produce the lithospheric thickness required here. We propose that the remnant plume material, which has a higher seismic velocity than the ambient mantle due to melt depletion and dehydration, significantly contributed to the thickening of the mantle lithosphere. Key Points: A negative interface at an average depth of 80 km is observed by receiver functions and interpreted as consolidated plume melts Early arrivals of the 410 and 660 phases suggest high velocities in the upper mantle, implying a thick lithosphere The lithosphere was thinned by the mantle plume during the Gondwana breakup and has been reconstructed by melt depletion and dehydration